Mortalidade, crescimento e solução do solo em eucalipto com aplicação de fertilizante de liberação lenta - da Silva, Paulo Henrique Muller; Poggiani, Fabio; Silva, Ariane Andre; Prada Neto, Ithamar; de Paula, Rinaldo Cesar [UNESP] (FapUNIFESP (SciELO), 2015)
Fertilization is one of the most effective ways to increase crop productivity, and the use of slow release fertilizers could be advantageous, allowing the assimilation of nutrients as the plants grow. The objective was evaluating the effect of slow release fertilizers in a Eucalyptus urophylla x E. grandis stand in order to reduce the number of fertilization applications. The experimental design was randomized blocks with four treatments. Treatments were applied with the same amounts of nutrients: T1-Convetional fertilizer with split application; T2-Conventional fertilizer in a single dose at 3 months; T3-Controlled-release fertilizer applied at planting; and T4-Controlled-release fertilizer applied 3 months after planting. We evaluated the mortality, initial growth, leaf nutrition and N and K in the soil solution. The experiment showed an average mortality of 4%, height of 8.5 m, DBH of 7.5 cm and volume of 24 m3.ha-1 at 18 months of age, with no difference among treatments for these characteristics. There were no differences in foliar concentrations of N, P, Ca, Mg and S, only the K differed among treatments, with the lowest concentration at conventional fertilizer split application treatment. The application of slow release fertilizer at 3 months showed the lowest concentrations of N and K in the soil solution. The split application of nutrients showed no improvement in eucalypt growth or nutritional benefits. The use of slow-release fertilizer is possible to reduce the number of fertilization application with no risk of nutrients leaching.
Mortality, initial growth and soil solution in eucalypts stands with slow release fertilization
Keywords: Leaching; Polyblen; Productivity; Split fertilization; Topdressing fertilization